ARTISTIC-AESTHETIC EXPRESSIVENESS OF INTERNAL SPACE IN THE ARCHITECTURE OF CENTRAL ASIA - D. M. Bayramova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The article is dedicated to the peculiarities of the internal space composition in architecture of Central Asia. There are some main distinguishing features of artistic and aesthetic functions of this direction considered. The purpose of the article is to find forms of ancient cultures interpretation in modern interiors, given the growing tendency of the traditional style use in architecture and design. There are some examples of tourism service facilities in the historic centers of the region with elements of national architecture given. Currently there is an increasing tendency of applying the traditional style in architecture and design using modern building materials. This makes the objects attractive for people interested in different cultures. Entire cities are becoming a modern interpretation of ancient cultures. In the case of designing tourist complexes near the monuments of culture, the direct study of their space-planning structure makes possible to identify the characteristics of the objects architecture, which will recreate the atmosphere of the cultural epoch of that time in a modern style.